Conflits latents et manifestes dans les pêcheries artisanales de l’écorégion de la Commission sous-régionale des pêches (CSRP) : tensions actuelles et défis futurs - El hadj Bara Dème; Grégoire Touron-Gardic; Pierre Failler (VertigO)
The aim of this study is to assess the factors exacerbating conflicts in artisanal fisheries in the SRFC ecoregion, and to question the ability of current management frameworks to resolve them. The method consisted in conducting interviews with various stakeholders in the SRFC countries, combining semi-structured interviews and focus groups to analyse the perceptions and dynamics of conflicts in artisanal fisheries. The results show that conflicts in SRFC artisanal fisheries are not solely linked to competition for access to resources but are the product of a combination of structural and interactional factors. On the one hand, structural factors, such as the influence of extractive industries, the extension of Marine Protected Areas, and management policies perceived as inequitable, reinforce power asymmetries and tensions linked to access to resources. On the other hand, interactional factors, such as internal rivalries between artisanal fishermen, frustrations with technological inequalities and uncertainties caused by climate change, aggravate conflict dynamics. These tensions are rooted in relationships of domination, perceptions of injustice and imbalances in the distribution of benefits, revealing a complexity that goes far beyond the struggle for resources alone. These conflicts are likely to intensify in the future with the expansion of protected fishing zones, such as MPAs and EBSAs, the intensification of artisanal fishermen's migration, and the overlap of extractive industries with these zones in developing countries. These dynamics, combined with the effects of climate change and the absence of regional conflict management mechanisms in frameworks such as the SRFC, will create an even more conflict-ridden and uncertain environment for artisanal fishers.